2014
DOI: 10.1542/peds.2014-0158
|View full text |Cite
|
Sign up to set email alerts
|

Duration and Course of Post-Concussive Symptoms

Abstract: OBJECTIVES: To examine the incidence, duration, and clinical course of individual post-concussive symptoms in patients presenting to a pediatric emergency department (ED) with a concussion. METHODS: We conducted secondary analysis of a prospective cohort study of patients 11 to 22 years old presenting to the ED of a children’s hospital with an acute concussion. The main outcome measure was duration of symptoms, assessed by th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

13
211
0
5

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 313 publications
(232 citation statements)
references
References 27 publications
13
211
0
5
Order By: Relevance
“…In 1 study conducted at a tertiary pediatric concussion clinic, emotional symptoms, including depression, frustration, irritability, and restlessness, were reported by 22.9%-27.7% of the patients evaluated less than 72 hours after injury. 7 Emotional symptoms peaked 7 days after injury and decreased to 8.3%-14.7% among patients who remained symptomatic at 28 days. Together, these findings confirm that emotional symptoms are reported in a substantial proportion of pediatric patients with SRC, can Ours is the first study to examine the prevalence, clinical features, risk factors, and management of postinjury psychiatric outcomes among pediatric patients with SRC referred to a multidisciplinary pediatric concussion program.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…In 1 study conducted at a tertiary pediatric concussion clinic, emotional symptoms, including depression, frustration, irritability, and restlessness, were reported by 22.9%-27.7% of the patients evaluated less than 72 hours after injury. 7 Emotional symptoms peaked 7 days after injury and decreased to 8.3%-14.7% among patients who remained symptomatic at 28 days. Together, these findings confirm that emotional symptoms are reported in a substantial proportion of pediatric patients with SRC, can Ours is the first study to examine the prevalence, clinical features, risk factors, and management of postinjury psychiatric outcomes among pediatric patients with SRC referred to a multidisciplinary pediatric concussion program.…”
Section: Discussionmentioning
confidence: 94%
“…Although many pediatric patients will recover to their neurological baseline within 1-4 weeks with an appropriate amount of physical and cognitive rest, 21%-73% of patients will experience symptoms that last longer than 1 month and will be diagnosed with postconcussion syndrome (PCS). 1,2,5,6,11,56 Although the impact of pediatric SRC on physical and cognitive functioning has been well documented in previous clinical research studies, 1,2,[5][6][7]11,37,56 there has been little attention paid to the emotional and psychiatric manifestations of this condition. Previous studies have observed novel psychiatric disorders (NPDs) occurring in 10%-100% of children and adolescents with TBI of various severities, including personality changes, attention-deficit hyperactivity disorder (ADHD), behavioral disorders, depression, and anxiety disorders.…”
mentioning
confidence: 99%
“…Symptoms from most concussions resolve in <2 weeks [8]; however, for some athletes the symptoms can persist for longer than 1 month [9]. In that intervening period, athletes may experience a combination of cognitive, somatic and emotional symptoms [9,10] that can impair their ability to complete school or work obligations [11].…”
Section: Introductionmentioning
confidence: 99%
“…In that intervening period, athletes may experience a combination of cognitive, somatic and emotional symptoms [9,10] that can impair their ability to complete school or work obligations [11]. Athletes who sustain more concussions are more likely to experience prolonged symptoms [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…It is often recommended to wait for resolution of symptoms before initiating a structured rehabilitation program [3,4,23], but based on our patient's circumstances the symptoms needed to be addressed more directly [24]. Our program regularly engages symptoms in rehabilitation designed to work around and address them so improvement can be achieved.…”
Section: Discussionmentioning
confidence: 99%